Letter - Stevenson, Daniel M., Sir
042-0038-001 Telegrams: "Stevenson, Cleveden, Glasgow" Telephone: West 2470 Scottish Ambulance Unit in Spain Commandant : Miss Fernanda Jacobsen, O.B.E. CLEVEDEN, GLASGOW Chairman: Sir Daniel Stevenson. Bart.. LL.D. Committee: Ishbel, Marchioness of Aberdeen and Temair, G.B.E. The Countess of Oxford and Asquith. Sir Henry Ballantyne William Black. Esq. The Right Hon. The Lord Provost, P. J. Dollan, Esq. Bailie Elger A. Forrester-Paton, Esq. The Hon. Mrs. Forrester-Paton Professor and Mrs. Glaister Sir Thomas and Lady Glen-Coats Mrs. John M. Hogg, Lenzie Miss Fernanda Jacobsen, O.B.E. Sir John Mann. K.B.E. Sir David Mason, LL.D. David Perry, Esq. Sir Andrew H. Pettigrew, LL.D. Ralph Risk, Esq., M.C. The Rt. Hon. Sir Archibald Sinclair, Bart. M.P. Lady Swan. Professor Walton. Lady Wilson. Secretary : Miss Williams. In affiliation with The National Joint Committee for Spanish Relief, Chairman: The Duchess of Atholl, D.B.E., LL.D. Vice-Chairmen: The Earl of Listowel Miss Eleanor Rathbone, M.P. Hon. Treasurer: Viscount Cecil of Chelwood, P.C., K.C. Hon Secretaries: Mr. D.R. Grenfell, M.P. Capt. J.R.J. Macnamara, M.P. Mr. Wilfrid Roberts, M.P. 19th. December 1938. Dear Mr. Tewson, I have a harrowing letter this morning from Miss Jacobsen, dated Madrid 4th. December. She cannot understand "why Barcelona and in fact all Catalonia is so short of food - every town, every village, every hamlet starving; no food anywhere and yet they are near the French Frontier, whereas Madrid's food has to go by sea to Valencia and thence some 300 miles by lorries to the sector where the Scottish Ambulance Unit works." I know and appreciate the difficulties you have dealing with appeals from many quarters, but you must excuse me again pressing for a substantial share of the T.U.C. collections for the Scottish Ambulance Unit. Our October and November consignments were shipped on credit and the last instalment was only paid the other day. Another substantial shipment left on 15th. December, the entire cost £2,384, has been advanced by our bankers on personal guarantee. Our bank account is slightly overdrawn and the position is really desperate. I hope you and your colleagues in Sir Walter's absence will make a special effort in our favour. Yours sincerely, D.M. Stevenson E.V. Tewson, Esq., Trades Union Congress, Transport House, Smith Square, London W.C.1 292/946/42/38